Profitabilitas, Financial Leverage Dan Perataan Laba - Nunuk Tri Utami; Febryandhie Ananda (Akuntansi, 2023)
Income smoothing is one of the efforts made by management to reduce fluctuations in profits earned so that profits match the desired target. Income smoothing is also a common form of earnings management. This is done with the motivation to show good performance to investors, by showing stable company profits. This study aims to analyze the effect of proofreadability and financial leverage on income smoothing in companies in the consumer goods industry sector that are listed on the Indonesian stock exchange in 2018-2021. The method used in this research is to use quantitative methods using secondary data. The sample collection technique used in this study was a purposive sampling technique which produced 58 selected company samples over a period of 4 years so that 232 company samples were obtained. The hypothesis in this study was tested using logistic regression analysis using the SPSS 22 program. The results of this study indicate that profitability and financial leverage have no effect on income smoothing.